The historical present in Thucydides semantics and narrative function = Le présent historique chez Thucydide : sémantique et fonction narrative - Lallot, Jean. (Amsterdam Studies in Classical Philology, 2011)
After Etudes sur l'aspect verbal chez Platon (Saint-Etienne, 2000), the international 'Groupe de recherche sur l'aspect verbal en grec' now presents a second volume on verbal aspect in (Ancient) Greek, which is devoted to the function(s) of the Historical Present in Thucydides. In nine chapters the authors approach this subject from a variety of angles, focusing inter alia on the HP of particular verbs and on its use in battle narratives, or investigate Thucydides' use of the HP from a comparative perspective. They share one important assumption, viz. that the primary function of the HP is to mark events that were, according to Thucydides, of decisive importance for the development of the Peloponnesian War. By its rich and detailed analyses the book provides important new insights into Thucydides' narrative technique.